Pengaruh Post Isometric Relaxation pada Kasus Myofascial Pain Syndrome Upper Trapezius terhadap Penurunan Nyeri di Ar – Rohmah Islamic Boarding School Malang - Safun Rahmanto; Kurnia Putri Utami; Eka Yanti Sri Utami (Jurnal Fisioterapi dan Rehabilitasi, 2020)
ABSTRACT Background: Myofascial pain syndrome is the situation of taut pain and tenderness pain, this syndrome is often found in trapezius muscle. The result of Preliminary study shows that the tahfidz program students in Ar – Rohmah Islamic Boarding School Malang spent time to learn Al – Qur’an for 6-8hour/day with static situation and complained about the pain in the neck. Purpose: To find out the effect of Post Isometric Relaxation on decrease pain of myofascial pain syndrome of the upper trapezius in Ar – Rohmah Islamic Boarding School Malang. Method: This study uses Pre-experimental one group pretest and posttest design. The respondents in this study are 26 students of thafidz program in Ar – Rohmah Islamic Boarding School Malang with technique of purposive sampling and were given intervention 3 times in a week for 2 weeks. Instrument of this research is Numerical Rating Scale (NRS) and the data analysis is using Wilcoxon test. Result: It shows 0,000 (α < 0,05) and show there is decrease pain from 0,742 to 0,633. Conclusion: There is an effect of post isometric relaxation on decrease the pain of myofascial pain syndrome of upper the trapezius in Ar – Rohmah Islamic Boarding School Malang.